Application of correlation as a measure of performance - Mohd. Rijal, O.; Mohd Noor, N.; Chang, Y.F. (2011)
Correlation generally shows the relationship between variables. A judicious use of this relationship may yield a measure of performance for a given algorithm. In this study the correlation measure Rp 2 derived from the Un replicated Linear Functional relationship (ULFR) model will be shown to be a useful measure of performance in selected procedure or algorithm for a particular image registration method, a medical treatment, a character recognition method, and a compression method. The main result of these numerical studies strongly suggests that Rp2 is potentially useful as a performance measure in a wide range of imaging problem.